Counselling via a "Death Perspective" - Seeman, Howard (Canadian Journal of Counselling and Psychotherapy, 2011)
The author points out that there has been much progress in the clinical literature in helping people deal with the event of death (e.g., working with the terminally ill, counselling someone who has lost a loved one, etc.). But, he argues, there is great neglect in the literature regarding viewing death as a perspective, and its valuable clinical use. By referring to Heidegger's contributions to existential psychology, he explains what he means by this perspective, how it can be used therapeutically in our counselling, and offers guidelines for its careful application.